1966
DOI: 10.1029/wr002i001p00059
|View full text |Cite
|
Sign up to set email alerts
|

Energy, total carbon, and oxygen demand

Abstract: The biodegradable content of organics in aqueous solution can be assessed in two ways: by measuring the change in organic content effected by bacterial metabolism; or by measuring the consumption of oxygen by bacteria in effecting the removal of organics. In addition to oxygen, two possible parameters for pollution measurement are thermodynamic energy change and total carbon change. The validity of applying thermodynamic concepts to biological systems is questioned. Total carbon changes during the process of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Whereas other workers (23,24,55,118) have reported incorporation of approximately 60 percent of the ca.rbon of substra.tes such as glucose and glycerol at the expense of the oxidized 40 percent, bacterium HR oxidized to CO2 approximately 75 per cent of the methane and alcohol carbon provided and incorporated only 2S percent. A greater demand for oxygen would logically be expected when a hydrocarbon is the sole carbon source since many of the carbohydrates, amino acids, and other cellular components are oxygenated compounds.…”
Section: Calculation Of Ymldsmentioning
confidence: 93%
See 1 more Smart Citation
“…Whereas other workers (23,24,55,118) have reported incorporation of approximately 60 percent of the ca.rbon of substra.tes such as glucose and glycerol at the expense of the oxidized 40 percent, bacterium HR oxidized to CO2 approximately 75 per cent of the methane and alcohol carbon provided and incorporated only 2S percent. A greater demand for oxygen would logically be expected when a hydrocarbon is the sole carbon source since many of the carbohydrates, amino acids, and other cellular components are oxygenated compounds.…”
Section: Calculation Of Ymldsmentioning
confidence: 93%
“…Additionally impressive evidence of the closeness of fit to approximately 0.6 of the ratio of substrate carbon assimilated to total utilized is found in studies of the aerobic growth of mixed cultures of soil and sewage bacteria at the expense of known quantities of "pure biochemicals" (24,119,120 Busch (23) observed that maximal microbial growth ("solids produc tion") occurred in sewage supplemented with glucose when (i) all of the sugar was utilized, and (ii) enough oxygen was consumed to indicate that 41 percent of the total had been oxidized. So dependable was this latter figure in a number of repetitions that it was then proposed (24,47) that cal culations based on this value (which can be easily and Quickly determined) might well be employed as the standard for estimation of BOD 2 in preference to waiting five days for an answer, as the most widely used method now necessitates.…”
Section: Oxidative Assimilation In Mixed Populationsmentioning
confidence: 94%
“…Before the application of the aerobic biological method (BS) to HWW, a control test for the experimental system is performed, using glucose (at 40 mg TOC L −1 , glucose is a reference substance for biodegradation [25 , 26] ) and measuring oxygen consumption. Once the proper performance of microorganisms is established, the BS is applied to the HWW sample for 36 h, also monitoring the oxygen consumption.…”
Section: Treatment Of the Target Pharmaceuticals In Hww By The Biolog...mentioning
confidence: 99%